Application of rivaroxaban in patients with non-valvular atrial fibrillation and end-stage kidney disease: A systematic review and meta-analysis - Yang, Zhenzhen; Wang, Jieya; Yuan, Ye; Cheng, Tian; Ren, Feifei; Wang, Songsong; Zhang, Zhiqing (Frontiers in Cardiovascular Medicine, 2023)
Nowadays, the number of patients with non-valvular atrial fibrillation (NVAF) complicated with end-stage renal disease (ESKD) is increasing. There are significant challenges in anticoagulation with prescription drugs because of the high risk of bleeding and embolism among these patients. However, the combination of Warfarin with any non-vitamin K antagonist oral anticoagulant (NOACs) have not been conducted in a randomized controlled trial in patients with baseline creatinine clearance < 25ml/min, which makes it difficult to justify the use of anticoagulants in such patients. Then, we aimed to collect and summarize all evidences to enable anticoagulation of rivaroxaban, which is less dependent on renal clearance, in patients with severe renal insufficiency, and to complement and improve the evidences on the use of rivaroxaban for anticoagulation. The present systematic review and Meta-analysis searched Databases of PubMed, Embase, Cochrane Library, CNKI, CBM and Google Scholar databases for relevant studies from inception to June 1,2022, with the restriction of English language and Chinese. Eligible Cohort studies and randomized controlled trials (RCTs) that reported efficacy outcome (composite of stroke and systemic embolism; ischemic stroke; systemic embolism) or safety outcomes (major bleeding; intracranial hemorrhage; gastrointestinal bleeding) of rivaroxaban in NVAF patients with ESRD were enrolled. Data extraction and study quality assessment by two authors independently, Cochrane Collaboration’s tool for assessing risk of bias was used for RCTs, and NEW-Castle Ottawa scale was used for study quality assessment for cohort studies. Dichotomous variables were calculated as Risk risks with 95% conﬁdence intervals, Meta-regression analysis was performed to explore the inﬂuence of study design, rivaroxaban dose and controlled drugs factors on outcomes. In this study, Low-dose rivaroxaban (10 mg, once a day) may benefit more than warfarin in patients with non-valvular atrial fibrillation and end-stage renal disease.